Obesity and Overweight Prevalence and Related Factors in Turkish Community - Pirincci, Edibe; Yakar, Burkay; Eren, Semih; Kaya, Ferit; Bulut, Irem; Acar, Ufuk; Deveci, Süleyman Erhan (My University, 2023)
Objective: The prevalence of obesity and overweight are increasing in all over the world. Better understanding of the relationships between obesity and related factors is necessary for effective prevention and management of obesity in Turkey. The current study was aimed to determine the obesity prevalence and factors related to obesity and to contribute to obesity prevention strategies. Methods: Population-based, cross-sectional study was conducted in eastern part of Turkey. The sample size was calculated as 1058 households with a deviation of 3% at 95% confidence interval from a total of 128,706 households. Sociodemographic characteristics, risk factors for obesity and antropometric measurements of the participants were obtained with the questionnaire form. The questionnaire “The WHO STEPwise approach to surveillance (STEPS)” was taken as a basis to determine risk factors. Body mass index of individuals was used in the diagnosis of overweight and obesity, and waist circumference was used in the diagnosis of central obesity. Results: Total of 1679 participants over aged 18 years, 55.9% (n=938) were female and 44.1% (n=741) were male. The prevalence of overweight and obesity were 34.0%, and 31.7% respectively. The prevalence of obesity was higher in women (40.9%) and the prevalence of overweight (34.0%) was higher in men. Central obesity prevalence was 15.1%. (13.5% in women and 17.0% in men). According to waist-to-hip ratio, 44.1% of the participants were risky for cardiovasculer diseases. Being married (OR, 1.95; 95% CI, 1.34-2.85), being housewife (OR, 2.33; 95% CI,1.49-3.64), non-smokers (OR, 1.40; 95% CI, 1.05-1.87), low education level (especially illiteracy) (OR, 2.30; 95% CI, 1.27-4.14), age, especially 45-54 age range (OR, 10.27; 95% CI, 5.91-17.83), and having hypertension (OR, 1.25; 95% CI, 0.25-0.40) were independent risk factors for obesity. Conclusion: Approximately one third of the study populaton were obese and one third were overweight. Obesity rate was higher in women and overweight rate was higher in men. The prevalence of overweight and obesity appears to be an severe problem in study population. Based on current study data, we recommend taking preventions to reduce the prevalence of overweight and obesity immediately to improve public health.
Keywords: Nüfus İstatistikleri Bilimi; Halk ve Çevre Sağlığı; Sağlık Politikaları ve Hizmetleri